Pedagogical Conditions and Challenges for the Development of Research Skills - Carla Leticia Paz Delgado; Lorenzo Estrada (Universidad Autónoma de Baja California, 2022)
This paper presents the results of a study that sought to analyze conditions and challenges in the research training of students of teaching. To this end, a questionnaire was administered to 299 students and interviews were conducted with 8 professors of courses aimed at strengthening research skills. A linear regression model and multilevel model were used to analyze quantitative data, while textual analysis was used for qualitative information. The results show that a system of favorable beliefs and conceptions about research, student profiles upon entry to the university, and curriculum structure all play an important role in developing skills. Also linked to research training are the form of study and the academic level and research performance of professors.